2012
DOI: 10.1002/asi.22629
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative and fractional strategies when journals are assigned to several subfields

Abstract: In many datasets, articles are classified into sub-fields through the journals in which they have been published. The problem is that many journals are assigned to a single sub-field, but many others are assigned to several sub-fields. This paper discusses a multiplicative and a fractional strategy to deal with this situation, and introduces a normalization procedure in the multiplicative case that takes into account differences in mean citation rates across sub-fields. The empirical part studies different asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…These 10 These results are of the same order of magnitude as those obtained for field citation distributions in the multiplicative case for different time periods, at different aggregation levels, and with a fixed or a variable citation window Li et al, 2013). For the fractional case, see Herranz and Ruiz-Castillo (2012a). aggregate results for 219 scientific sub-fields, as well as the corresponding standard deviations and coefficients of variation, are extremely similar as those found in this paper for the definition of individual productivity as mean citation per article per person and authors are classified in 30 broad fields (row III in Table 3). …”
Section: Comparison Of Results With the Previous Literaturesupporting
confidence: 73%
“…These 10 These results are of the same order of magnitude as those obtained for field citation distributions in the multiplicative case for different time periods, at different aggregation levels, and with a fixed or a variable citation window Li et al, 2013). For the fractional case, see Herranz and Ruiz-Castillo (2012a). aggregate results for 219 scientific sub-fields, as well as the corresponding standard deviations and coefficients of variation, are extremely similar as those found in this paper for the definition of individual productivity as mean citation per article per person and authors are classified in 30 broad fields (row III in Table 3). …”
Section: Comparison Of Results With the Previous Literaturesupporting
confidence: 73%
“…However, gap differences are not very large: only in 20 cases, of which 17 reflect a worsening of the EU situation, this difference in absolute value is 10 % greater than the US/EU gap under the multiplicative strategy. As in Herranz and Ruiz Castillo (2012a), the similarity of citation characteristics of articles published in journals assigned to one or several sub fields guarantees that choosing one of the two strategies may not lead to a radically different picture in this practical application. Secondly, after raising the Critical Citation Line from the 80th to the 95th percentile of world citation distributions the EU is ahead of the US in exactly the same number of sub fields as before, namely, 30.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the space of articles is expanded as much as necessary beyond the geographical extended count in what we call the double extended sub field count, which in our case reaches 6,512,031 articles or 57.7 % more than the number of articles in the geographical extended count. However, this is not that worrisome in the sense that, since this strategy does not create any interdependencies among the sub fields involved, it is still possible to sepa rately investigate every sub field in isolation, independently of what takes place in any other sub field (see Herranz and Ruiz Castillo (2012a) for a comparison of the two strategies).…”
Section: Assignment Of Articles To Geographical Areas and To Sub Fieldsmentioning
confidence: 99%
“…As in Herranz and Ruiz-Castillo (2011a), it can be shown that the number of articles and citations in the …”
Section: The Multiplicative Strategy In the Geographical Extenmentioning
confidence: 92%
“…As advocated in Herranz and Ruiz-Castillo (2011a), there are two reasons why the multiplicative strategy might be preferable to deal with this problem.…”
Section: Reasons For the Multiplicative Strategymentioning
confidence: 99%